The future of South East Asian rainforests in a changing landscape and climate. - Hector, A; Fowler, D; Nussbaum, R; Weilenmann, M; Walsh, R (2011)
With a focus on the Danum Valley area of Sabah, Malaysian Borneo, this special issue has as its theme the future of tropical rainforests in a changing landscape and climate. The global environmental context to the issue is briefly given before the contents and rationale of the issue are summarized. Most of the papers are based on research carried out as part of the Royal Society South East Asia Rainforest Research Programme. The issue is divided into five sections: (i) the historical land-use and land management context; (ii) implications of land-use change for atmospheric chemistry and climate change; (iii) impacts of logging, forest fragmentation (particularly within an oil palm plantation landscape) and forest restoration on ecosystems and their functioning; (iv) the response and resilience of rainforest systems to climatic and land-use change; and (v) the scientific messages and policy implications arising from the research findings presented in the issue.